Lithium iron phosphate positive electrode material, preparation method thereof and lithium ion battery

Through carbon coating modification and palladium and fluorine co-doping technology, the lithium iron phosphate material was modified to solve the problem of poor electrochemical performance of LiFePO4 positive electrode material, significantly improve the conductivity and structural stability of the material, and achieve more efficient lithium ion diffusion and electrochemical properties.

CN119890296AActive Publication Date: 2025-04-25HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510019251.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-25
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

The existing LiFePO4 as a cathode material for lithium batteries has problems with poor electrochemical performance in actual use, including low lithium ion diffusion coefficient, poor electrochemical performance, low theoretical density and low tap density.

Method used

Through carbon coating modification and palladium and fluorine co-doping technology, lithium iron phosphate materials are modified to improve their conductivity and structural stability. The specific steps include selecting a specific metal palladium and fluorine co-doping, carbon-coated modified lithium iron phosphate material, and achieving a uniform gel state by defining the material mixing sequence and heating and stirring at different temperatures.

Benefits of technology

The electrochemical performance of lithium iron phosphate materials has been significantly improved, including the first charging specific capacity, the first discharge specific capacity and the charge and discharge efficiency. Compared with the unmodified materials, the charge and discharge efficiency is improved by 3%, and the effect is obvious.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890296A_ABST
    Figure CN119890296A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium iron phosphate positive electrode material, a preparation method thereof and a lithium ion battery, and belongs to the technical field of batteries. The structural formula of the lithium iron phosphate positive electrode material is Li < 1 + y > Fe < 1-x > Pd < x > PO < 4 > F < y > / C, 0 lt; x is less than or equal to 0.3, 0lt; and y < = 0.5. The preparation method comprises the following steps: obtaining raw materials including a lithium source, an iron source, a palladium source, a phosphorus source, a fluorine source and a carbon source according to an atomic ratio; mixing a lithium source, an iron source, a palladium source, a phosphorus source, a fluorine source and a carbon source to prepare mixed powder; and carrying out heat treatment on the mixed powder in an inert atmosphere to obtain the lithium iron phosphate positive electrode material. In the material, palladium and fluorine are selected for co-doping, so that the electronegativity of the LiFePO4 material can be improved, the intrinsic conductivity and the surface conductivity of the LiFePO4 material are enhanced, the electrochemical performance of the material is effectively improved, and the material is stable in structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Lithium-ion battery refers to a secondary battery system that uses two different lithium-intercalation compounds as the positive and negative electrodes of the battery, respectively. The structure of the lithium-intercalation compound can reversibly insert and remove lithium ions. The materials of lithium-ion batteries are mainly composed of four parts: positive electrode material, negative electrode material, separator and electrolyte. Among them, for every 50% increase in the specific capacity of the positive electrode active material, the energy density of the battery will increase by 28% accordingly. It can be seen that the positive electrode material of lithium-ion batteries is a key influencing factor in increasing the energy density of the battery, improving the stability of cycle performance and reducing the cost of the battery. The positive electrode materials that have been widely used at present have defects in both performance and preparation cost, and cannot meet the needs of energy storage equipment and power tools for power lithium-ion batteries. Therefore, it has become an inevitable trend to develop new materials with excellent properties such as good structural stability, abundant raw material resources and low preparation cost.

[0003] Goodenough's research team first proposed that the olivine-structured LiFePO4 material has the performance of lithium extraction / insertion. LiFePO4 has attracted widespread attention as a new type of positive electrode material for lithium-ion batteries. The main advantages of LiFePO4 materials include wide raw material sources, environmental friendliness, high theoretical specific capacity (170 mAh / g) and stable discharge platform. Compared with layered materials, its more prominent advantage is that the phosphate ions of LiFePO4 materials are very stable anion groups, which will not decompose and release oxygen during the charge and discharge process, and the volume strain of the material itself is small. At the same time, the crystal structure of LiFePO4 and the charged product orthorhombic iron phosphate (FePO4) is similar, which makes LiFePO4 materials have good safety stability, thermal stability and long cycle life. Therefore, it is considered to be one of the most promising positive electrode materials for power lithium-ion batteries.

[0004] Although LiFePO4 has great advantages as a positive electrode material for lithium-ion batteries, there are still many problems in the process of synthesis and practical application: ferrous ions are easily oxidized during synthesis and easily agglomerate during heat treatment; the lithium ion diffusion coefficient is relatively low and the electrochemical performance is poor; the theoretical density is low and the tap density is low. Summary of the invention

[0005] The main purpose of the present invention is to provide a lithium iron phosphate positive electrode material and a preparation method thereof and a lithium ion battery, so as to solve the problem that LiFePO4 as a lithium battery positive electrode material in the prior art still has poor electrochemical performance in actual use.

[0006] In order to achieve the above object, according to one aspect of the present invention, a lithium iron phosphate positive electrode material is provided, and its structural formula is as follows:

[0007] Li 1+y Fe 1-x Pd x PO4F y / C Formula I;

[0008] In Formula I, 0 <x≤0.3,0<y≤0.5;

[0009] Furthermore, in Formula I, 0.01≤x≤0.2, 0.01≤y≤0.3; preferably 0.05≤x≤0.2, 0.1≤y≤0.3. The present application adopts the above structural ratio, which is beneficial to improving the electrochemical properties of lithium iron phosphate materials, especially electrical conductivity and structural stability.

[0010] Furthermore, in the structure of the lithium iron phosphate positive electrode material, palladium and fluorine are co-doped in the lithium iron phosphate, and the outer surface of the lithium iron phosphate is coated with a carbon material.

[0011] The present invention performs carbon coating modification ( / C) on LiFePO4. The carbon material has good electrical conductivity and can further improve the surface conductivity of LiFePO4. The present invention selects specific metal cations palladium and fluorine to co-dope the carbon-coated lithium iron phosphate. The doped metal palladium ions can further improve the intrinsic conductivity and surface conductivity of lithium iron phosphate. The particle size of LiFePO4 is small, which can reduce the Li + Migration distance, increasing Li + The diffusion rate of the lithium iron phosphate material is increased, and the doped fluorine element can stabilize the structure of the lithium iron phosphate material. The present invention uses carbon coating surface modification and palladium and fluorine co-doping internal modification. The two modification methods work together synergistically to improve the overall conductivity of the lithium iron phosphate material, thereby improving its electrochemical performance.

[0012] Furthermore, the median particle size D50 of the lithium iron phosphate positive electrode material is 0.3~0.6μm, and the morphology is spherical.

[0013] According to the second aspect of the present application, a method for preparing the above-mentioned lithium iron phosphate positive electrode material is provided, and the method comprises the following steps:

[0014] Step S1: obtaining a lithium source, an iron source, a palladium source, a phosphorus source, a fluorine source and a carbon source according to the ratio of each element;

[0015] Step S2: mixing a lithium source, an iron source, a palladium source, a phosphorus source, a fluorine source and a carbon source to prepare a mixed powder;

[0016] Step S3: heat the mixed powder in an inert atmosphere to obtain a lithium iron phosphate positive electrode material.

[0017] Further, in step S1, the molar ratio of Li element in the lithium source, Fe element in the iron source, Pd element in the palladium source, P element in the phosphorus source, F element in the fluorine source, and C element in the carbon source is (1 + y):(1 - x):x:1:y:(3 - 6); where 0 < x ≤ 0.2, 0 < y ≤ 0.3; preferably, 0.01 ≤ x ≤ 0.2, 0.01 ≤ y ≤ 0.3; more preferably, 0.05 ≤ x ≤ 0.2, 0.05 ≤ y ≤ 0.3; even more preferably, 0.05 ≤ x ≤ 0.15, 0.15 ≤ y ≤ 0.25.

[0018] Further, in step S1, the lithium source is selected from one or more of lithium hydroxide monohydrate, lithium oxide, lithium peroxide, lithium oxalate, lithium hydroxide, lithium carbonate, lithium phosphate, lithium nitrate, and lithium chloride.

[0019] Further, the iron source is selected from one or more of iron powder, iron phosphate, ferrous oxalate, ferrous acetate, and iron nitrate.

[0020] Further, the palladium source is selected from one or more of palladium on carbon, , and in the one or more.

[0021] Further, the phosphorus source is selected from one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid, and ammonium phosphate.

[0022] Further, the fluorine source is selected from one or more of lithium fluoride, iron fluoride, and sodium fluoride.

[0023] Further, the carbon source is selected from one or more of citric acid, glucose, glycine, sucrose, ascorbic acid, and polyvinyl alcohol.

[0024] The composite material prepared by the above specific raw materials such as the lithium source, iron source, palladium source, phosphorus source, fluorine source, and carbon source selected in the present invention has better electrochemical performance; those skilled in the art can select from the prior art according to actual needs.

[0025] Further, in step S2, first, the lithium source, iron source, palladium source, phosphorus source, fluorine source, carbon source, and organic solvent are mixed to form a gel; then the gel is dried to form a mixed powder.

[0026] Further, the organic solvent includes an alcohol solvent, and the alcohol solvent is ethylene glycol.

[0027] Further, in step S2, the carbon source and the iron source are dissolved in water, stirred until completely dissolved, the phosphorus source, lithium source, palladium source, and fluorine source are added, and stirred to form a mixed solution; ethylene glycol is added to the mixed solution, stirred until a gel is formed; the gel is dried under vacuum and ground to obtain a mixed powder.

[0028] Furthermore, in step S2, the carbon source and the iron source are dissolved in water and stirred at a temperature of 60°C to 100°C until completely dissolved; the phosphorus source and the lithium source are added, and magnetic stirring is performed for 1h to 4h in a water bath environment at a temperature of 70°C to 100°C to form a mixed solution; the palladium source, the fluorine source and ethylene glycol are added to the mixed solution, and magnetic stirring is performed for 1h to 5h in an oil bath condition at 100°C to 140°C until a gel is formed.

[0029] The present invention is more conducive to the full dissolution of each material by limiting the material mixing order. By heating and stirring different raw materials at different temperatures, targeted dissolution and mixing of each raw material can be achieved according to the characteristics of different raw materials, so that each raw material is fully dissolved and forms a uniform gel state.

[0030] Furthermore, in step S3, the mixed powder is first subjected to a preliminary calcination treatment in an inert atmosphere to obtain a preliminary calcination product, the preliminary calcination product is ground to obtain a ground product; and the ground product is then calcined in an inert atmosphere to obtain a lithium iron phosphate positive electrode material.

[0031] Furthermore, the conditions of the initial calcination treatment include: a heating rate of 1-5°C / min, a temperature of 350-400°C, and a time of 3.5-4.5h.

[0032] Furthermore, the calcination conditions include: a heating rate of 1-2°C / min, a temperature of 650°C-800°C, and a calcination time of 6-12h.

[0033] The present invention adopts the calcination conditions to make the carbon-coated, palladium-fluorine co-doped and iron phosphate series materials more stably and uniformly modified lithium iron phosphate materials, so as to improve the electrochemical performance of the modified lithium iron phosphate materials.

[0034] Further, the inert atmosphere includes an argon atmosphere or a nitrogen atmosphere.

[0035] According to a third aspect of the present application, a positive electrode material is provided. The positive electrode material is the above-mentioned lithium iron phosphate positive electrode material or the lithium iron phosphate positive electrode material prepared by the above-mentioned method.

[0036] According to a fourth aspect of the present application, a lithium-ion battery is provided, comprising a positive electrode material, which is the positive electrode material described above.

[0037] The technical solution of the present invention is applied to provide a lithium iron phosphate positive electrode material, in which the carbon coating layer can be used as a conductive layer, which can improve the conductivity of the surface of the particles of the LiFePO4 material; at the same time, the carbon coating layer can inhibit the grain growth of the material, obtain LiFePO4 particles with smaller particle size, and reduce the Li + Migration distance, increasing Li + The diffusion rate of Fe is reduced during the heat treatment process.2+ Oxidation is carried out to obtain a LiFePO4 cathode material with relatively high purity. Selecting palladium and fluorine co-doping in this material can increase the electronegativity of the LiFePO4 material, enhance the intrinsic conductivity and surface conductivity of the LiFePO4 material, effectively improve the electrochemical performance of the material, and the structure of the material is stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The accompanying drawings forming a part of this application are used to provide a further understanding of the present invention. The schematic embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation to the present invention.

[0039] Figure 1 Shows the SEM image of the cathode material Li 1.2 Fe 0.85 Pd 0.15 PO4F 0.2 / C prepared in Example 1 of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0040] It should be noted that, without conflict, the embodiments in this application and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0041] Since there are defects in the synthesis and practical process of LiFePO4, such as the ferrous ions are easily oxidized during the synthesis process and easily agglomerate during heat treatment; the lithium ion diffusion coefficient is relatively low and the electrochemical performance is poor; the theoretical density is low and the tap density is relatively low, the present invention selects specific metal palladium and fluorine co-doped carbon-coated modified lithium iron phosphate material, which improves the electrochemical performance of lithium iron phosphate.

[0042] The present invention provides a lithium iron phosphate cathode material, and its structural formula is as follows:

[0043] Li 1+y Fe 1-x Pd x PO4F y / C Formula I;

[0044] In Formula I, 0 < x ≤ 0.3, 0 < y ≤ 0.5; x is the molar number of palladium element, y is the molar number of fluorine element, 1 + y is the molar number of lithium element, 1 - x is the molar number of iron element, and the molar number of phosphorus element is 1;

[0045] In the structure of the above formula I, the value of x can be selected from any value among 0.01, 0.03, 0.05, 0.08, 0.10, 0.12, 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.3, or any range between two thereof; the value of y can be selected from any value among 0.01, 0.03, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.3, 0.32, 0.35, 0.38, 0.4, 0.42, 0.45, 0.48, 0.5, or any range between two thereof.

[0046] The present invention performs carbon coating modification ( / C) on LiFePO4. The carbon material has good electrical conductivity and can further improve the surface conductivity of LiFePO4. The present invention selects specific metal cations palladium and fluorine to co-dope the carbon-coated lithium iron phosphate. The doped metal palladium ions can further improve the intrinsic conductivity and surface conductivity of lithium iron phosphate. The particle size of LiFePO4 is small, which can reduce the Li + Migration distance, increasing Li + The diffusion rate of the lithium iron phosphate material is increased, and the doped fluorine element can stabilize the structure of the lithium iron phosphate material. The present invention uses carbon coating surface modification and palladium and fluorine co-doping internal modification. The two modification methods work together synergistically to improve the overall conductivity of the lithium iron phosphate material, thereby improving its electrochemical performance. The first charge specific capacity of the modified lithium iron phosphate material can reach up to 163 mAh / g, the first discharge specific capacity can reach up to 157 mAh / g, and the first charge and discharge efficiency can reach 96%. Compared with the prior art, the first charge and discharge efficiency of lithium iron phosphate modified by only carbon coating is increased by 3% at most, and the improvement effect is very obvious.

[0047] As a specific implementation, the structure of the lithium iron phosphate positive electrode material is that palladium and fluorine are co-doped in the lithium iron phosphate, and the surface of the lithium iron phosphate is coated with a carbon material.

[0048] As a specific implementation, the particle size of the lithium iron phosphate positive electrode material is 0.3 μm to 0.6 μm and the morphology is spherical.

[0049] As a specific implementation, in Formula I, 0.01≤x≤0.3, 0.01≤y≤0.5; 0.01≤x≤0.2, 0.01≤y≤0.3 may be selected; 0.05≤x≤0.2, 0.1≤y≤0.3 may be further selected; 0.05≤x≤0.15, 0.15≤y≤0.25 may be further selected; for example, x=0.1, y=0.2. The above structural ratio is beneficial to improving the electrochemical properties of lithium iron phosphate materials, especially the conductivity and structural stability.

[0050] The present invention provides a method for preparing the above-mentioned lithium iron phosphate cathode material, comprising the following steps:

[0051] Step S1: Obtain raw material lithium source, iron source, palladium source, phosphorus source, fluorine source and carbon source according to the molar ratio of each element in Formula I;

[0052] Step S2: Mix the lithium source, iron source, palladium source, phosphorus source, fluorine source and carbon source to form a mixed powder;

[0053] Step S3: Heat-treat the mixed powder in an inert atmosphere to obtain the lithium iron phosphate cathode material.

[0054] The preparation method of the present invention is simple in operation, the raw materials are easy to obtain, the prepared lithium iron phosphate modified material has small particles, the particle size D 50 is 0.3 μm to 0.6 μm, such as 0.45 μm, the morphology is spherical, and the electrochemical performance of the material is significantly improved compared with that of lithium iron phosphate before modification.

[0055] As a specific embodiment, in step S1, the molar ratio of Li element in the lithium source, Fe element in the iron source, Pd element in the palladium source, P element in the phosphorus source, F element in the fluorine source and C element in the carbon source is (1 + y): (1 - x): x: 1: y: (3 to 6); wherein, 0 < x ≤ 0.3, 0 < y ≤ 0.5; the value of x can be selected from any value or the range value between any two of 0.01, 0.03, 0.05, 0.08, 0.10, 0.12, 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.3; the value of y can be selected from any value or the range value between any two of 0.01, 0.03, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.20, 0.22, 0.25, 0.28, 0.3, 0.32, 0.35, 0.38, 0.4, 0.42, 0.45, 0.48, 0.5. For example, 0.01 ≤ x ≤ 0.3, 0.01 ≤ y ≤ 0.5; preferably 0.05 ≤ x ≤ 0.2, 0.05 ≤ y ≤ 0.3; more preferably 0.05 ≤ x ≤ 0.15, 0.15 ≤ y ≤ 0.25; for example, x = 0.1, y = 0.2. Adopting the above more optimal structural ratio is more beneficial to improving the electrochemical performance of the lithium iron phosphate material, especially the conductivity and structural stability.

[0056] The molar ratio of the C element in the carbon source is selected from any value among 3, 4, 5, 6 or a range value between any two of them; specifically, the molar ratio of the Li element in the lithium source, the Fe element in the iron source, the Pd element in the palladium source, the P element in the phosphorus source, the F element in the fluorine source and the C element in the carbon source can be selected as (1.1~1.3): (0.85~0.95): (0.05~0.15): 1: (0.1~0.3): 4.5. Under the above raw material ratio conditions, the first charge specific capacity, first discharge specific capacity and first discharge efficiency of the modified lithium iron phosphate material are significantly improved, such as the first charge and discharge efficiency reaches 95.5~96.2%; when the molar ratio of Li element in the lithium source, Fe element in the iron source, Pd element in the palladium source, P element in the phosphorus source, F element in the fluorine source and C element in the carbon source in the raw material formula is 1.2:0.9:0.1:1:0.2:4.5, the first charge specific capacity, first discharge specific capacity and first discharge efficiency of the modified lithium iron phosphate material are better improved, such as the first charge and discharge efficiency reaches about 96.2%.

[0057] In the preparation method of the present invention, the lithium source can be selected from one or more of lithium hydroxide monohydrate, lithium oxide, lithium peroxide, lithium oxalate, lithium hydroxide, lithium carbonate, lithium phosphate, lithium nitrate, and lithium chloride; the iron source is selected from one or more of iron powder, ferric phosphate, ferrous oxalate, ferrous acetate, and ferric nitrate; the palladium source is selected from palladium carbon, , and One or more of; the phosphorus source is selected from one or more of ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid and ammonium phosphate; the fluorine source is selected from one or more of lithium fluoride, ferric fluoride and sodium fluoride; the carbon source is selected from one or more of citric acid, glucose, glycine, sucrose, ascorbic acid and polyvinyl alcohol. The composite material prepared by the specific raw materials such as the lithium source, iron source, palladium source, phosphorus source, fluorine source, carbon source selected by the present invention has better electrochemical performance; those skilled in the art can select from the existing technology according to actual needs.

[0058] In step S2 of the preparation method of the present invention, a lithium source, an iron source, a palladium source, a phosphorus source, a fluorine source, a carbon source and an organic solvent are first mixed to form a gel; and then the gel is dried to form a mixed powder, wherein the organic solvent includes an alcohol solvent, preferably ethylene glycol. The steps of preparing the gel in this process are not limited, as long as the raw materials are mixed and stirred until they are in a gel state, and the order of mixing the raw materials is not limited; the steps of preparing the gel into the mixed powder are not limited, as long as the gel can be prepared into a powder.

[0059] As a specific implementation of step S2, in this process, the carbon source and the iron source can be first dissolved in water and stirred until completely dissolved, and then the phosphorus source, lithium source, palladium source and fluorine source are added and stirred to form a mixed solution; finally, ethylene glycol is added to the mixed solution and stirred until a gel is formed; and the obtained gel is vacuum dried and then ground to obtain a mixed powder.

[0060] As a more specific implementation of step S2, the carbon source and the iron source can be dissolved in water, and stirred at 60°C to 100°C until completely dissolved; the phosphorus source and the lithium source are added, and magnetic stirring is performed for 1h to 4h in a water bath environment at 70°C to 100°C to form a mixed solution; the palladium source, the fluorine source and the ethylene glycol are added to the mixed solution, and magnetic stirring is performed for 1h to 5h in an oil bath at 100°C to 140°C until a gel is formed. In this preferred embodiment, by limiting the order of mixing the materials, it is more conducive to the full dissolution of each material, and by heating and stirring different raw materials at different temperatures, it is possible to achieve targeted dissolution and mixing of each raw material according to the characteristics of different raw materials, so that each raw material is fully dissolved and forms a uniform gel state.

[0061] As a specific implementation of step S3, the mixed powder can be first subjected to a preliminary calcination treatment in an inert atmosphere to obtain a preliminary calcination product, and the preliminary calcination product can be ground to obtain a ground product; and the ground product can be calcined in an inert atmosphere to obtain a palladium and fluorine co-doped carbon-coated lithium iron phosphate material. By first low-temperature preliminary calcination, cooling grinding, and high-temperature calcination, uniform heat treatment can be obtained, the lithium iron phosphate particles have a small particle size that is beneficial to electrical properties, carbon, palladium, and fluorine can be fully combined with lithium iron phosphate, and the carbon coating modification effect is good, and palladium and fluorine are uniformly co-doped, so that the final structure of the lithium iron phosphate material is more stable.

[0062] As a more specific implementation of step S3, the conditions of the initial calcination treatment include: a heating rate of 1-5°C / min, a temperature of 350°C-400°C, and a time of 3.5-4.5h.

[0063] As a more specific implementation of step S3, the calcination conditions include: a heating rate of 1-2°C / min, a temperature of 650°C-800°C, and a time of 6 h-12 h. Under the calcination conditions, the carbon-coated, palladium-fluorine co-doped and iron phosphate column materials can be more stably and uniformly modified lithium iron phosphate materials, so as to improve the electrochemical properties of the modified lithium iron phosphate materials.

[0064] In the above-mentioned embodiment, the inert atmosphere includes an argon atmosphere or a nitrogen atmosphere; nitrogen can be selected in practical applications.

[0065] The present invention provides a positive electrode material, specifically a lithium ion battery polyanion positive electrode material, which can be a lithium iron phosphate positive electrode material prepared by the above method.

[0066] The present invention provides a lithium ion battery, the positive electrode material of which can adopt the lithium ion battery polyanion positive electrode material of the present invention.

[0067] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0068] Example 1 (Li 1.2 Fe 0.95 Pd 0.05 PO4F 0.2 / C material)

[0069] 0.2 mol of lithium carbonate, 0.38 mol of iron powder, 0.4 mol of phosphoric acid, 0.02 mol of palladium chloride, 0.08 mol of lithium fluoride and 1.8 mol of citric acid were weighed according to the molar ratio of Li:Fe:P:Pd:F:citric acid=1:0.95:1:0.05:0.2:4.5, and 0.6 mol of ethylene glycol was weighed. The citric acid and iron powder were dissolved in water, stirred at 90°C until completely dissolved, and then lithium carbonate and phosphoric acid were added, and magnetic stirring was performed at 90°C for 4 hours to form a mixed solution; ethylene glycol was then added, and magnetic stirring was performed in an oil bath at 120°C for 3 hours until a gel was formed; the gel was vacuum dried and ground to obtain a mixed powder; the mixed powder was heated to 350°C at a rate of 2°C / min in a nitrogen-filled tubular furnace and low-temperature calcined for 4 hours; the obtained product was taken out and ground again, and then heated to 750°C at a rate of 2°C / min in a nitrogen-filled tubular furnace and high-temperature calcined for 1 hour, and then cooled with the furnace, and the obtained product was ground to obtain Li 1.2 Fe 0.95 Pd 0.05 PO4F 0.2 / C materials, such as Figure 1 shown.

[0070] Example 2 (Preparation of Li 1.2 Fe 0.9 Pd 0.1 PO4F 0.2 / C material)

[0071] 0.2 mol of lithium carbonate, 0.36 mol of iron powder, 0.4 mol of phosphoric acid, 0.04 mol of palladium chloride, 0.08 mol of lithium fluoride and 1.8 mol of citric acid were weighed according to the molar ratio of Li:Fe:P:Pd:F:citric acid=1:0.9:1:0.1:0.2:4.5, and 0.6 mol of ethylene glycol was weighed. The citric acid and iron powder were dissolved in water, stirred at 90°C until completely dissolved, and then lithium carbonate and phosphoric acid were added, and magnetic stirring was performed at 90°C for 4 hours to form a mixed solution; ethylene glycol was then added, and magnetic stirring was performed at 120°C in an oil bath for 3 hours until a gel was formed; the gel was vacuum dried and ground to obtain a mixed powder; the mixed powder was heated to 350°C at a rate of 2°C / min in a nitrogen-filled tubular furnace and low-temperature calcined for 4 hours; the obtained product was taken out and ground again, and then heated to 750°C at a rate of 2°C / min in a nitrogen-filled tubular furnace and high-temperature calcined for 1 hour, and then cooled with the furnace, and the obtained product was ground to obtain Li 1.2 Fe 0.9 Pd 0.1 PO4F 0.2 / C material.

[0072] Example 3 (Preparation of Li 1.2 Fe 0.85 Pd 0.15 PO4F 0.2 / C material)

[0073] 0.2 mol of lithium carbonate, 0.34 mol of iron powder, 0.4 mol of phosphoric acid, 0.06 mol of palladium chloride, 0.08 mol of lithium fluoride and 1.8 mol of citric acid were weighed according to the molar ratio of Li:Fe:P:Pd:F:citric acid=1:0.85:1:0.15:0.2:4.5, and 0.6 mol of ethylene glycol was weighed. The citric acid and iron powder were dissolved in water, stirred at 90°C until completely dissolved, and then lithium carbonate and phosphoric acid were added, and magnetic stirring was performed at 90°C for 4 hours to form a mixed solution; ethylene glycol was then added, and magnetic stirring was performed at 120°C in an oil bath for 3 hours until a gel was formed; the gel was vacuum dried and ground to obtain a mixed powder; the mixed powder was heated to 350°C at a rate of 2°C / min in a nitrogen-filled tubular furnace and low-temperature calcined for 4 hours; the obtained product was taken out and ground again, and then heated to 750°C at a rate of 2°C / min in a nitrogen-filled tubular furnace and high-temperature calcined for 1 hour, and then cooled with the furnace, and the obtained product was ground to obtain Li 1.2 Fe 0.85 Pd 0.15 PO4F 0.2 / C material.

[0074] Example 4 (Preparation of Li 1.1 Fe 0.85 Pd0.15 PO4F 0.1 / C material)

[0075] The difference between Example 4 and Example 3 is that the raw material ratio is different. 0.2 mol of lithium carbonate, 0.34 mol of iron powder, 0.4 mol of phosphoric acid, 0.06 mol of palladium chloride, 0.04 mol of lithium fluoride and 1.8 mol of citric acid are weighed according to the molar ratio of Li:Fe:P:Pd:F:citric acid=1:0.85:1:0.15:0.1:4.5.

[0076] Example 5 (Preparation of Li 1.3 Fe 0.85 Pd 0.15 PO4F 0.3 / C material)

[0077] The difference between Example 5 and Example 3 is that the raw material ratio is different. 0.2 mol of lithium carbonate, 0.34 mol of iron powder, 0.4 mol of phosphoric acid, 0.06 mol of palladium chloride, 0.12 mol of lithium fluoride and 1.8 mol of citric acid are weighed according to the molar ratio of Li:Fe:P:Pd:F:citric acid=1:0.85:1:0.15:0.3:4.5.

[0078] Comparative Example 1 (Preparation of LiFePO4 / C Material)

[0079] 0.2 mol lithium carbonate, 0.4 mol iron powder, 0.4 mol phosphoric acid, 1.8 mol citric acid, and 0.6 mol ethylene glycol were weighed according to the molar ratio of Li:Fe:P:citric acid = 1:1:1:4.5. The citric acid and iron powder were dissolved in water, stirred at 90°C until completely dissolved, and then lithium carbonate and phosphoric acid were added, and magnetic stirring was performed at 90°C for 4 hours to form a mixed solution; then ethylene glycol was added, and magnetic stirring was performed at 120°C oil bath conditions for 3 hours until a gel was formed; the gel was vacuum dried and ground to obtain a mixed powder; the mixed powder was heated to 350°C at a rate of 2°C / min in a nitrogen-filled tubular furnace and initially calcined for 4 hours; the obtained product was taken out and ground again, and then heated to 750°C at a rate of 2°C / min in a nitrogen-filled tubular furnace and calcined for 1 hour, and then cooled with the furnace, and the obtained product was ground to obtain LiFePO4 / C material.

[0080] Comparative Example 2 (Preparation of Li 1.1 FePO4F 0.1 / C)

[0081] According to the molar ratio of Li:Fe:P:F:citric acid = 1:1:1:0.1:4.5, 0.2 mol of lithium carbonate, 0.4 mol of iron powder, 0.4 mol of phosphoric acid, 0.04 mol of lithium fluoride and 1.8 mol of citric acid were weighed, and 0.6 mol of ethylene glycol was weighed. The citric acid and iron powder were dissolved in water, stirred at 90°C until completely dissolved, and then lithium carbonate and phosphoric acid were added, and magnetic stirring was performed at 90°C for 4 hours to form a mixed solution; then ethylene glycol was added, and magnetic stirring was performed at 120°C oil bath conditions for 3 hours until a gel was formed; the gel was vacuum dried and ground to obtain a mixed powder; the mixed powder was heated to 350°C at a rate of 2°C / min in a nitrogen-filled tubular furnace and low-temperature calcined for 4 hours; the obtained product was taken out and ground again, and then heated to 750°C at a rate of 2°C / min in a nitrogen-filled tubular furnace and high-temperature calcined for 1 hour, and then cooled with the furnace, and the obtained product was ground to obtain Li 1.1 FePO4F 0.1 / C material.

[0082] Comparative Example 3 (Preparation of Li 1.2 FePO4F 0.2 / C)

[0083] According to the molar ratio of Li:Fe:P:F:citric acid = 1:1:1:0.2:4.5, 0.2 mol of lithium carbonate, 0.4 mol of iron powder, 0.4 mol of phosphoric acid, 0.08 mol of lithium fluoride and 1.8 mol of citric acid were weighed, and 0.6 mol of ethylene glycol was weighed. The citric acid and iron powder were dissolved in water, stirred at 90°C until completely dissolved, and then lithium carbonate and phosphoric acid were added, and magnetic stirring was performed at 90°C for 4 hours to form a mixed solution; then ethylene glycol was added, and magnetic stirring was performed at 120°C oil bath conditions for 3 hours until a gel was formed; the gel was vacuum dried and ground to obtain a mixed powder; the mixed powder was heated to 350°C at a rate of 2°C / min in a nitrogen-filled tubular furnace and low-temperature calcined for 4 hours; the obtained product was taken out and ground again, and then heated to 750°C at a rate of 2°C / min in a nitrogen-filled tubular furnace and high-temperature calcined for 1 hour, and then cooled with the furnace, and the obtained product was ground to obtain Li 1.2 FePO4F 0.2 / C material.

[0084] Comparative Example 4 (Preparation of Li 1.3 FePO4F 0.3 / C material)

[0085] According to the molar ratio of Li:Fe:P:F:citric acid = 1:1:1:0.3:4.5, 0.2 mol of lithium carbonate, 0.4 mol of iron powder, 0.4 mol of phosphoric acid, 0.12 mol of lithium fluoride and 1.8 mol of citric acid were weighed, and 0.6 mol of ethylene glycol was weighed. The citric acid and iron powder were dissolved in water, stirred at 90°C until completely dissolved, and then lithium carbonate and phosphoric acid were added, and magnetic stirring was performed at 90°C for 4 hours to form a mixed solution; then ethylene glycol was added, and magnetic stirring was performed at 120°C oil bath conditions for 3 hours until a gel was formed; the gel was vacuum dried and ground to obtain a mixed powder; the mixed powder was heated to 350°C at a rate of 2°C / min in a nitrogen-filled tubular furnace and low-temperature calcined for 4 hours; the obtained product was taken out and ground again, and then heated to 750°C at a rate of 2°C / min in a nitrogen-filled tubular furnace and high-temperature calcined for 1 hour, and then cooled with the furnace, and the obtained product was ground to obtain Li 1.3 FePO4F 0.3 / C material.

[0086] Table 1

[0087]

[0088] It can be seen from Table 1 that the fluorine and palladium co-doped carbon-coated lithium iron phosphate materials prepared in Examples 1 to 5 of the present invention have a first charge specific capacity of 159.4 to 163.3 mAh / g, a first discharge specific capacity of 152.9 to 157.1 mAh / g, and a first charge efficiency of 95.5% to 96.2%; while the lithium iron phosphate materials prepared in Comparative Examples 1 to 4 have a first charge specific capacity of 149.9 to 154.3 mAh / g, a first discharge specific capacity of 139.7 to 149.1 mAh / g, and a first charge efficiency of 93.2% to 95.6%; in comparison, the first charge and discharge efficiency of the fluorine and palladium co-doped carbon-coated lithium iron phosphate materials prepared in Examples 1 to 5 of the present invention is increased by about 3%, which is more obvious in the research and development technology in this field.

[0089] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0090] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A lithium iron phosphate positive electrode material, characterized in that: Its structural formula is as follows: Li 1+y Fe 1-x Pd x PO4F y / C of formula I; In Formula I, 0 <x≤0.3,0<y≤0.5。 2. The lithium iron phosphate positive electrode material according to claim 1, characterized in that: In formula I, 0.01≤x≤0.2, 0.01≤y≤0.3; preferably 0.05≤x≤0.2, 0.1≤y≤0.3; And / or, in the structure of the lithium iron phosphate positive electrode material, palladium and fluorine are co-doped in the lithium iron phosphate, and the outer surface of the lithium iron phosphate is coated with a carbon material; And / or, the median particle size D50 of the lithium iron phosphate positive electrode material is 0.3-0.6 μm, and the morphology is spherical.

3. The method for preparing the lithium iron phosphate positive electrode material according to claim 1 or 2, characterized in that: The method comprises the following steps: Step S1: obtaining a lithium source, an iron source, a palladium source, a phosphorus source, a fluorine source and a carbon source according to the ratio of each element; Step S2: mixing the lithium source, the iron source, the palladium source, the phosphorus source, the fluorine source and the carbon source to prepare a mixed powder; Step S3: heating the mixed powder in an inert atmosphere to obtain the lithium iron phosphate positive electrode material.

4. The method for preparing the lithium iron phosphate positive electrode material according to claim 3, characterized in that: In step S1, the molar ratio of the Li element in the lithium source, the Fe element in the iron source, the Pd element in the palladium source, the P element in the phosphorus source, the F element in the fluorine source and the C element in the carbon source is (1+y): (1-x): x: 1: y: (3-6); wherein 0 <x≤0.3,0<y≤0.5; Preferably, 0.01≤x≤0.2, 0.01≤y≤0.3; further preferably, 0.05≤x≤0.2, 0.05≤y≤0.3; even more preferably, 0.05≤x≤0.15, 0.15≤y≤0.

25.

5. The method for preparing the lithium iron phosphate positive electrode material according to claim 3 or 4, characterized in that: In step S1, the lithium source is selected from one or more of lithium hydroxide monohydrate, lithium oxide, lithium peroxide, lithium oxalate, lithium hydroxide, lithium carbonate, lithium phosphate, lithium nitrate and lithium chloride; And / or, the iron source is selected from one or more of iron powder, ferric phosphate, ferrous oxalate, ferrous acetate and ferric nitrate; And / or, the palladium source is selected from palladium carbon, , and One or more of; and / or, the phosphorus source is selected from one or more of diammonium phosphate, diammonium hydrogen phosphate, phosphoric acid and ammonium phosphate; And / or, the fluorine source is selected from one or more of lithium fluoride, iron fluoride and sodium fluoride; And / or, the carbon source is selected from one or more of citric acid, glucose, glycine, sucrose, ascorbic acid and polyvinyl alcohol.

6. The method for preparing the lithium iron phosphate positive electrode material according to any one of claims 3 to 5, characterized in that: In step S2, the lithium source, the iron source, the palladium source, the phosphorus source, the fluorine source, the carbon source and an organic solvent are first mixed to form a gel; and then the gel is dried to obtain the mixed powder; Preferably, the organic solvent comprises an alcohol solvent; the alcohol solvent is ethylene glycol; Preferably, in step S2, the carbon source and the iron source are dissolved in water, stirred until completely dissolved, the phosphorus source, the lithium source, the palladium source and the fluorine source are added, stirred to form a mixed solution; ethylene glycol is added to the mixed solution, stirred until a gel is formed; the gel is dried under vacuum and then ground to obtain the mixed powder; Preferably, in the step S2, the carbon source and the iron source are dissolved in water and stirred at a temperature of 60°C to 100°C until completely dissolved; the phosphorus source and the lithium source are added, and magnetic stirring is performed for 1h to 4h in a water bath environment at a temperature of 70°C to 100°C to form a mixed solution; the palladium source, the fluorine source and the ethylene glycol are added to the mixed solution, and magnetic stirring is performed for 1h to 5h in an oil bath condition at 100°C to 140°C until a gel is formed.

7. The method for preparing a lithium iron phosphate positive electrode material according to any one of claims 3 to 6, characterized in that: In step S3, the mixed powder is first subjected to a primary calcination treatment in an inert atmosphere to obtain a primary calcination product, and the primary calcination product is ground to obtain a ground product; and the ground product is then calcined in an inert atmosphere to obtain the lithium iron phosphate positive electrode material.

8. The method for preparing a lithium iron phosphate positive electrode material according to claim 7, characterized in that: The conditions of the initial calcination treatment include: a heating rate of 1-5°C / min, a temperature of 350-400°C, and a time of 3.5-4.5h; And / or, the calcination conditions include: a heating rate of 1-2°C / min, a temperature of 650°C-800°C, and a time of 6-12h; And / or, the inert atmosphere is an argon atmosphere or a nitrogen atmosphere.

9. A positive electrode material, characterized in that: The positive electrode material comprises the lithium iron phosphate positive electrode material according to claim 1 or 2 or the lithium iron phosphate positive electrode material prepared by the method according to any one of claims 3 to 8.

10. A lithium ion battery comprising a positive electrode material; characterized in that: The positive electrode material is the positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Lithium ion phosphate cathode material of lithium ion battery and preparation method

    CN102340004A

  • Multi-ion-doped carbon-coated lithium iron phosphate battery material and preparation method thereof

    CN103367746A

  • Positive electrode material for lithium ion battery and preparation method thereof

    CN109192935A

  • Preparation method of modified lithium iron phosphate

    CN115676799A

  • Fluorine-containing lithium iron phosphate composite material and preparation method and application thereof

    CN116525797A